A Comparative Analysis of Metadiscourse Markers in Pakistani and Native English Travel Blogs - Bibi, Hafsa; Ishaq, Samina; Anwaar, Zarmina (Pakistan Languages and Humanities Review, 2024)
This study seeks to investigate metadiscourse markers utilized by travel bloggers in both Pakistani English and Native English contexts. Metadiscourse functions as an interaction tool employed by writers to foster a sense of self-reflection and facilitate reciprocal engagement with their readers. In the contemporary context, the burgeoning tourism industry and the widespread use of social media have led to an accelerated exchange of ideas. Employing a mixed- methods analysis, the research focused analysis of interactive and interactional metadiscourse, using Hyland’s (2005) Interpersonal Model of Metadiscourse. The researchers employed a convenient sampling technique to collect 15 travel blogs in both Pakistani English and Native English. Findings show that Pakistani English bloggers extensively use both interactional and interactive metadiscourse markers compared to their Native English counterparts. The analysis highlights the prevalence of boosters, transitions, hedges, engagement markers, and self-mentions among bloggers, indicating common strategies. This study reveals cross-cultural nuances in travel blogging by examining metadiscourse markers in both contexts. The findings contribute to a deeper understanding of how language influences reader engagement and shapes travel experiences, offering insights valuable for bloggers, linguists, and the tourism industry. The research suggests more in-depth study of metadiscourse markers as an interaction tool across different genres.